The Gulf Stream influence on wintertime North Atlantic jet variability - O'Reilly, C; Minobe, S; Kuwano-Yoshida, A; Woollings, T (Wiley, 2016)
In this paper we investigate the influence of the Gulf Stream SST front on the North Atlantic eddy-driven jet and its variability, by analysing the NCEP-CFSR dataset and a pair of AGCM simulations forced with realistic and smoothed Gulf Stream SST boundary conditions. The Gulf Stream SST front acts to generate stronger meridional eddy heat flux in the lower-troposphere and an eddy-driven jet over the eastern North Atlantic that is located further polewards, compared to the simulation with smoothed SST. The strong Gulf Stream SST gradient is found to be crucial in more accurately capturing the trimodal distribution of the eddy-driven jet latitude, with the more poleward climatological jet being the result of the jet occupying the northern jet position more frequently in the simulation forced with observed SSTs. The more frequent occurence of the northern jet location is associated with periods of high eddy heat flux over the Gulf Stream region. Composite analysis of high eddy heat flux events reveals that the significantly higher heat flux is followed by larger and more persistient poleward jet excursions in the simulations with realistic SSTs compared to the simulation with smoothed SSTs, with upper-tropospheric eddy momentum fluxes acting to maintain the more poleward eddy-driven jet. Periods of high eddy heat flux over the Gulf Stream region are also shown to be associated with increased blocking frequency over Europe, which are clearly distinct from periods with a northern jet position.